Integrated transcriptomic and metabolic profiling reveals the molecular mechanism of improved nitrogen metabolism in walnut (Juglans regia L.) roots mediated by soybean intercropping - Ren, Jing; Liu, Xiaoyong; Wang, Yifeng; Jiang, Xuefeng; Chen, Yaonian (Frontiers in Plant Science, 2026)
IntroductionThe practice of intercropping young walnut orchards with soybeans has emerged as a promising approach within the framework of sustainable agricultural management. However, the precise impacts of soybean intercropping on nitrogen metabolism in walnut roots remain insufficiently elucidated.MethodsIn this study, ‘Yuanlin’ walnut and ‘Longhuang 3’ soybean were used as experimental materials, with two planting patterns established: walnut monoculture and walnut-soybean intercropping. A combination of metabolomics, transcriptomics (RNA-seq), and physiological index determination was employed to systematically investigate the regulatory mechanisms of nitrogen metabolism in walnuts under the intercropping system.Results and discussionThe results showed that the dry matter accumulation of both aboveground tissues and roots in intercropped walnuts was significantly higher than that in monocropped walnuts, with the root system had a distinct vertical growth advantage. The nitrogen content in aboveground portions during dormancy and in roots during the hard kernel stage and dormancy was markedly elevated compared to monoculture systems. Metabolomics analysis revealed that differential metabolites in walnut under intercropping are significantly enriched in the carbon-nitrogen metabolic pathways and nitrogen transmembrane transport pathways. RNA-seq analysis identified 3,978 differentially expressed genes (DEGs), with significantly enrichment in the “nitrogen utilization” pathway. Furthermore, integrated analysis indicated that nitrogen metabolites may play a significant role in the walnut intercropping system. Key genes associated with nitrogen metabolism (NR, NIR, GOGAT, GDH, NRT, and AMT) exhibited significant alterations under the intercropping system. Enzyme activity validation demonstrated that intercropping substantially enhanced the activities of GS, GOGAT, and other enzymes, thereby strengthening the GS/GOGAT cycle responsible for converting inorganic nitrogen into organic nitrogen. This study confirms that walnut-soybean intercropping promotes dry matter accumulation and nitrogen allocation by activating root carbon-nitrogen metabolic pathways and the expression of nitrogen metabolism-related genes. These findings provide critical metabolic and transcriptional evidence supporting the sustainable development of intercropping systems in dryland orchards.